A child's introduction to poetry - Driscoll, Michael, 1973-; Hamilton, Meredith (New York : Black Dog & Leventhal Publishers : Distributed by Workman Pub., 2003)
This wide-ranging journey through the history and highlights of the world's poetry covers everything from epics and odes to nonsense verse and haikus, and includes a full-length CD! Hey there! I'm Professor Driscoll, and I'll be your guide as we explore the wonderful world of poetry, a fun and exciting place where anything can happen through the magic power of words. Get ready to visit imaginary lands filled with fascinating creatures like "Jabberwocks", or to travel backwards in time over 2,000 years to ancient Greece, or to be transported to far-away places like mountains, meadows, or big city streets. On the first part of our journey we'll get to know all the different types of poetry with their weird and wonderful names like lyric, haiku, sonnet, and villanelle. During the second part we'll get to meet some of the most famous poets of all time. Brilliant men and women such as William Shakespeare, Emily Dickinson, Robert Frost, Maya Angelou, and many more, who have used their imaginations to create all of the wonderful places and people we'll read about in this book. Best of all, we can listen to the poems being read aloud as we read along on the page. Every time you see the PLAY TRACK symbol you'll know it's time to listen to the CD and hear the poetry come to life. So, turn the page. Turn on your CD player. Turn on your imagination and let's be on our way!
Introducing Professor Driscoll: Rhymes and their reasons: Poems of cradles and bough-breakings, too, moon-jumping cows and ten kids in a shoe (Nursery rhymes) -- Rhymes that prompt laughter (If that's what you're after) (Nonsense verse) -- Nineteen lines but just two rhymes (Villanelle) -- There once was a poem so outrageous, read aloud, it became quite contagious (Limerick) -- Haikus have three lines and seventeen syllables simple, beautiful (Haiku) -- Gather round for a story of heroes and glory (Narrative verse) -- My dear, aren't you smitten by these words that I've written? (Lyric verse) -- Poem fantastic (Though usually old) that may teach a lesson (So it's often retold) (Ballad) -- Sheep, shepherds, and other sappy stuff (Pastoral) -- Poems of feelings and hearts shining bright (They're a pleasure to hear, but a devil to write) (Sonnet) -- When you haven't got time to think of a rhyme (Free verse) -- Alphabet poems, riddles, epitaphs, and other unusual styles (Poems peculiar) -- Poetry's greats: Rulers of rhyme, legends of the lyric and superstars of the spoken word: First poet: Homer (c. 700-800 B.C.) -- Bard: William Shakespeare (1564-1616) -- Free spirit: John Milton (1608-1674) --Artist: William Blake (1757-1827) -- People's poet: William Wordsworth (1770-1850) -- Daughter, wife, and poet: Elizabeth Barrett Browning (1806-1861) -- Poet of "Fantastic Terrors": Edgar Allan Poe -- Rebel without applause: Emily Dickinson (1830-1886) -- Voice of America: Walt Whitman (1819-1892) -- Poet of heaven and earth: Christina Rossetti (1830-1894) -- Poems of everyday beauty: Robert Frost (1875-1963) -- Adventurer: Robert Louis Stevenson (1850-1894) -- Englishman in Bombay: Rudyard Kipling (1863-1936) -- Good poet for bad children: Hilaire Belloc (1870-1953) -- American spirit: Carl Sandburg (1878-1967) -- Thinker: W.H. Auden (1907-1973) -- Brave new voice: Langston Hughes (1902-1967) -- Beat of the city: Lawrence Ferlinghetti (1919- ) -- Irish eye: Seamus Heaney (1939- ) -- Visions of Mexico: Octavio Paz (1914-1998) -- Caged bird's song: Maya Angelou (1928- ).
Includes bibliographical references (page 93).
Anne Bobby, John Kolvenbach.
Keywords: Children's poetry; Books on compact disc